2014
DOI: 10.1111/mec.12634
|View full text |Cite
|
Sign up to set email alerts
|

Population size and time since island isolation determine genetic diversity loss in insular frog populations

Abstract: Understanding the factors that contribute to loss of genetic diversity in fragmented populations is crucial for conservation measurements. Land-bridge archipelagoes offer ideal model systems for identifying the long-term effects of these factors on genetic variations in wild populations. In this study, we used nine microsatellite markers to quantify genetic diversity and differentiation of 810 pond frogs (Pelophylax nigromaculatus) from 24 islands of the Zhoushan Archipelago and three sites on nearby mainland … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
88
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(100 citation statements)
references
References 81 publications
10
88
1
Order By: Relevance
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 82%
“…As shown in Figure 2, an obvious correlation can be inferred between the levels of genetic diversity and the population density. Our results are in accordance with studies in other species in which a similar correlation was found (Aspi et al 2006;Berthier et al 2006;Eckert et al 2008;Frankham 1996;Furlan et al 2012;Montgomery et al 2000;Wang et al 2013), including other rodents (Krebs 2013) and hamster species (Romanenko et al 2007), like the greater longtailed hamster (Dong et al 2010;Xie and Zhang 2006;Xu et al 2013a;Xue et al 2014), the golden hamster (Karsten et al 2005), and the common hamster (Banaszek et al 2012;Neumann et al 2005). Similarly, the genetic diversity of the striped hamster has experienced a trend of continuous decline in recent years.…”
Section: Genetic Diversity and Genetic Differentiationsupporting
confidence: 82%
“…These findings contrast with recent studies in either region, indicating that recent artificial 'islanding' in the TIL region can lead to significant loss of genetic diversity, especially in short-lived herbs (Yuan et al, 2012). Moreover, in the Zhoushan Archipelago, it was recently demonstrated that overwater distance is a significant barrier to contemporary gene flow in both pond frogs (Wang et al, 2014) and fig wasps (Liu et al, 2013), whereby in either instance genetic drift following Holocene island formation likely decreased diversity and increased differentiation among insular populations. By contrast, this study on L. chinense is the first to highlight the importance of gene flow (most likely via seed) in sustaining genetic diversity and preventing inter-population differentiation in the face of habitat 'insularization' in both the TIL region and the Zhoushan Archipelago, that is, at different temporal and spatial scales.…”
Section: Discussioncontrasting
confidence: 55%
“…This hypothesis is further suggested by the fact that the natural landscapes of the Zhoushan Archipelago have been greatly modified by human activities over the last 20 years, whereby the impervious surface area continues to increase at an average rate of 1.97 km 2 per year . Although certain agricultural developments also may have positive effects for some organisms, for example, frogs, for which irrigated fields provide suitable habitats (Knutson et al, 2004;Wang et al, 2014), much of the natural vegetation cover (that is, subtropical evergreen broad-leaved forest) has now been destroyed . Evidently, more finescale studies, using precise deforestation records, highly resolving molecular (for example, genomics) approaches, and a dense sampling, are required to determine whether such recent forest fragmentation has already affected the genetic architecture of constituent species, such as L. chinense.…”
Section: No Major Effects Of Island Characteristics On Genetic Diversitymentioning
confidence: 99%
See 2 more Smart Citations